History Learning Innovation with Steam Approach - Nur Aeni Marta; Otto Fajarianto; C. Santi Muji Utami (JTP - Jurnal Teknologi Pendidikan, 2023)
So far, history lessons are only textual in nature. For this reason, teachers must start preparing students to face the rapidly changing technological developments. Meanwhile, the need for human resources in the future is to be able to think analytically, collaboratively, and interdisciplinary. For this reason, this research will raise the application of STEAM through Project Based Learning as an innovation in learning history. Researchers use qualitative methods. First, reflection aims to bring students into the context of the problem and provide inspiration to students. At the research stage, more learning processes occur. In this stage, the teacher also guides the discussion more and determines whether students have developed conceptual and relevant understanding. The discovery stage connects research and information known in project preparation. Students begin to study independently and determine what is still unknown. At this stage, the students collaborate to find solutions. At the application stage, students test products made from previously determined conditions. The results obtained are used to improve the previous step. The final step is communication. The communication process is carried out to convey ideas. At this stage, the teacher and colleagues conduct a final assessment. In addition, teachers are also expected to be able to provide appreciation and constructive feedback. The results showed that STEAM in Project Based Learning for history learning proved to be effective in encouraging students’ creativity, collaboration, and communication skills. However, this method requires careful planning. Some students are also not familiar with project learning.